The Union One-Stop Shop as an instrument for the EU to achieve simplification of VAT obligations for intra-Community distance sellers - Inga Höft (2022)
Intra-Community distance sales occur in various constellations within commonly carried out transactions in the connection with e-commerce. However, the EU has recognised the administrative burdens, the compliance costs, and the complexity of VAT obligations for suppliers thereof and has developed different simplification aims and frameworks to overcome these hindrances. One practical measure that has been implemented as of 1 July 2021 is the Union One-Stop Shop. Hence, this thesis assesses in how far the Union One-Stop Shop is a viable instrument for the EU to achieve the simplification aims for intra-Community distance sellers, using a practical approach to analyse common scenarios and examine the goodness and effectiveness of the regulation. In practice, the Union One-Stop Shop is only partially a good and effective regulation for achieving a simplification of VAT obligations for intra-Community distance sellers, as various common transactions are not considered and covered by the Union scheme and certain local requirements remain obligatory.
Keywords: intra-community distance sales; Union One-Stop Shop; VAT compliance; e-commerce